Crime and punishment a concise moral critique - Gross, Hyman (Oxford : Oxford University Press, 2012)
Presenting an engaging critique of current criminal justice practice in the UK and USA, this book introduces central questions of criminal law theory. It develops a forceful argument that the prevailing justifications for punishment are misguided, and have resulted in the systematic infliction of unnecessary human misery.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Criminal justice, Administration of -- Great Britain -- Philosophy; Criminal justice, Administration of -- United States -- Philosophy; Punishment -- Great Britain -- Philosophy; Punishment -- United States -- Philosophy; Criminal justice, Administration of -- Moral and ethical aspects -- Great Britain; Criminal justice, Administration of -- Moral and ethical aspects -- United States; Punishment -- Moral and ethical aspects -- Great Britain; Punishment -- Moral and ethical aspects -- United States